Dithiolato- and halogenido-bridged nickel–iron complexes related to the active site of [NiFe]-H2ases: preparation, structures, and electrocatalytic H2 production. Issue 30 (20th July 2017) - Song, Li-Cheng; Han, Xiao-Feng; Chen, Wei; Li, Jia-Peng; Wang, Xu-Yong
Abstract : A new series of [NiFe]-H2 ase mimics (5a, b–7a, b ) has been prepared and structurally characterized; particularly, they have been found to be pre-catalysts for H2 production from Cl2 CHCO2 H under CV conditions. Abstract : A new series of the structural and functional models for the active site of [NiFe]-H2 ases has been prepared by a simple and convenient synthetic route. Thus, treatment of diphosphines RN(PPh2 )2 (1a, R = p -MeC6 H4 CH2 ;1b, R = EtO2 CCH2 ) with an equimolar NiCl2 ·6H2 O, NiBr2 ·3H2 O, and NiI2 in refluxing CH2 Cl2 /MeOH or EtOH gave the mononuclear Ni complexes RN(PPh2 )2 NiX2 (2a, R = p -MeC6 H4 CH2, X = Cl;2b, R = EtO2 CCH2, X = Cl;3a, R = p -MeC6 H4 CH2, X = Br;3b, R = EtO2 CCH2, X = Br;4a, R = p -MeC6 H4 CH2, X = I;4b, R = EtO2 CCH2, X = I) in 67–97% yields. Further treatment of complexes2a, b–4a, b with an equimolar mononuclear Fe complex (dppv)(CO)2 Fe(pdt) and NaBF4 resulted in formation of the targeted model complexes [RN(PPh2 )2 Ni(μ-pdt)(μ-X)Fe(CO)(dppv)](BF4 ) (5a, R = p -MeC6 H4 CH2, X = Cl;5b, R = EtO2 CCH2, X = Cl;6a, R = p -MeC6 H4 CH2, X = Br;6b, R = EtO2 CCH2, X = Br;7a, R = p -MeC6 H4 CH2, X = I;7b, R = EtO2 CCH2, X = I) in 60–96% yields. All the new complexes3a, b–4a, b and5a, b–7a, b have been characterized by elemental analysis and spectroscopy, and particularly for some of them (3a, b /4a, b and5b /6b ) by X-ray crystallography. More interestingly, the electrochemical and electrocatalytic properties of such halogenido-bridged model complexes are first studied systematically and particularly they have been found to be pre-catalysts for proton reduction to H2 under CV conditions.